Adjuvants for peptide-based cancer vaccines - Willem W Overwijk; Hiep Khong (Journal for ImmunoTherapy of Cancer)
Cancer therapies based on T cells have shown impressive clinical benefit. In particular, immune checkpoint blockade therapies with anti-CTLA-4 and anti-PD-1/PD-L1 are causing dramatic tumor shrinkage and prolonged patient survival in a variety of cancers. However, many patients do not benefit, possibly due to insufficient spontaneous T cell reactivity against their tumors and/or lacking immune cell infiltration to tumor site. Such tumor-specific T cell responses could be induced through anti-cancer vaccination; but despite great success in animal models, only a few of many cancer vaccine trials have demonstrated robust clinical benefit. One reason for this difference may be the use of potent, effective vaccine adjuvants in animal models, vs. the use of safe, but very weak, vaccine adjuvants in clinical trials. As vaccine adjuvants dictate the type and magnitude of the T cell response after vaccination, it is critical to understand how they work to design safe, but also effective, cancer vaccines for clinical use. Here we discuss current insights into the mechanism of action and practical application of vaccine adjuvants, with a focus on peptide-based cancer vaccines.